Universiti Malaysia Pahang’s students overseas - Irene, Wei Kiong Ting (2018)
“My exchange has been an amazing experience for me. I cannot deny that I faced difficulties in understanding the locals’ English accent, as I came over here with no knowledge of their culture etc. However, as time has passed, this experience gets better every day. I would cherish all experience and life-long knowledge I gained from this exchange,” said an exchange student who went to SRM Institute of Science and Technology, Chennai, India.